Electromagnetic Interference with Implantable Cardioverter Defibrillators Causing Inadvertent Shock: Case Report and Review of Current Literature. Issue 8 (January 2014) - Akhtar, Muhammad; Bhat, Tariq; Tantray, Mohmad; Lafferty, Chris; Faisal, Saiful; Teli, Sumaya; Bhat, Hilal; Raza, Muhammad; Khalid, Mariam; Biekht, Soad
As the number of patients having implantable cardioverter defibrillator (ICD) devices is increasing, it is important for the physicians and patients to be aware of situations and conditions that can result in interference with normal functioning of these devices. There are multiple cases of malfunction of ICDs reported in literature and it may be of great significance to have an overview of these incidents for appropriate recognition and future prevention. Here we are reviewing the available literature as well as reporting an interesting case of electromagnetic interference (EMI) resulting from leak of current in pool water causing firing of ICD.